2020
DOI: 10.3390/agronomy10010106
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi and Associated Microbiota as Plant Biostimulants: Research Strategies for the Selection of the Best Performing Inocula

Abstract: Arbuscular mycorrhizal fungi (AMF) are beneficial soil microorganisms establishing mutualistic symbioses with the roots of the most important food crops and playing key roles in the maintenance of long-term soil fertility and health. The great inter- and intra-specific AMF diversity can be fully exploited by selecting AMF inocula on the basis of their colonization ability and efficiency, which are affected by fungal and plant genotypes and diverse environmental variables. The multiple services provided by AMF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(102 citation statements)
references
References 108 publications
(142 reference statements)
0
93
0
9
Order By: Relevance
“…Briglia et al [64] demonstrated that the combination of phenomic (high-throughput plant phenotyping) and genomic (Next Generation Sequencing) tools opens new perspectives to release effective biostimulant formulations to meet the emerging needs of crops. Finally, Giovannini et al [65] suggested that, in the near future, transcriptomics research should be adopted as an integrated tool to identify the best synergistic combinations of AMF and associated bacterial communities able to enhance resources use efficiency, plant resilience and boosting nutraceutical compounds in plant species.…”
Section: Conclusion and Looking Forwardmentioning
confidence: 99%
“…Briglia et al [64] demonstrated that the combination of phenomic (high-throughput plant phenotyping) and genomic (Next Generation Sequencing) tools opens new perspectives to release effective biostimulant formulations to meet the emerging needs of crops. Finally, Giovannini et al [65] suggested that, in the near future, transcriptomics research should be adopted as an integrated tool to identify the best synergistic combinations of AMF and associated bacterial communities able to enhance resources use efficiency, plant resilience and boosting nutraceutical compounds in plant species.…”
Section: Conclusion and Looking Forwardmentioning
confidence: 99%
“…A promising strategy to enhance plant nutrition and thus plant performance is through the development of tripartite associations with bacteria and mycorrhizal fungi ( Wu et al , 2005 , Artursson et al , 2006 ; Bonfante and Anca, 2009 , Giovannini et al , 2020 ). AMF are in some cases associated with other microbes in the rhizosphere.…”
Section: Improvement In Plant Nitrogen Nutrition By Combining Bacterimentioning
confidence: 99%
“…In this review, we provide an overview of the major steps involved in N acquisition by plants, with a particular emphasis on the contribution of beneficial microorganisms that extract N from the soil or fix dinitrogen (N 2 ) from the atmosphere before its transfer to the plant. Possible synergistic interactions between these microorganisms is also discussed, as it may offer an avenue for the improvement of plant productivity through the enhancement of N acquisition ( Giovannini et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the future, a promising strategy to improve plant N nutrition could involve both bacteria and AM fungi, favoring the establishment of so-called tripartite associations [ 77 ]. In some cases, it has been found AMF associate with other microbes (mostly with bacteria) with beneficial or detrimental effects to AMF, although such relationships are not well characterized yet [ 78 , 79 ].…”
Section: Am Symbiosis-mediated Nitrogen Acquisition In Plantmentioning
confidence: 99%
“…In this line, a recent report showed that an AMF inoculum combined with a microbial consortium isolated from non-fertilized soils, leads to N uptake improvement in Brachypodium dystachion [ 81 ]. In addition, several plant-associated fungi, including AMF, are often colonized by endosymbiont (e.g., diazotrophs) that can provide additional N to the fungus, thus ameliorating plant N acquisition and physiological performances, particularly under poor fertilized soil environments [ 77 , 82 , 83 ]. Recently, de Novais and colleagues [ 84 ] demonstrated that the wide network of extraradical mycelium (ERM) in the soil can facilitate translocation and associations of beneficial bacteria (e.g., nitrogen-fixing rhizobia) and fungi to the colonized-plants, as also observed in AM-colonized fenugreek plants under water deficit conditions [ 79 ].…”
Section: Am Symbiosis-mediated Nitrogen Acquisition In Plantmentioning
confidence: 99%